Flavonoids from Epimedium pubescens: extraction and mechanism, antioxidant capacity and effects on CAT and GSH-Px of Drosophila melanogaster - Yang,Xiao-Hua; Li,Lu; Xue,Yao-Bi; Zhou,Xue-Xue; Tang,Jie-Hua (PeerJ, 2020)
Background Epimedium is a famous medicinal plant in China, Southeast Asian and some other regions. Flavonoids are regarded as its supremely important active constituents used in phytomedicines and/or functional foods. It is of theoretical and applied significance to optimize the procedure for extraction of flavonoids with high bioactivity from Epimedium, to unveil extraction mechanism, to identify chemical composition of flavonoids, to analyze free radical-scavenging ability of flavonoids, and to investigate their effects on the model organism Drosophila melanogaster. Methods Box-Behnken design was applied to optimization of extraction procedure. Laser diffraction particle size analysis was used to clarify extraction mechanism. Chemical composition of flavonoids was analyzed using high-performance liquid chromatography. Antiradical capacities of flavonoids were determined by chemical-based assay. Then, effects of flavonoids on catalase (CAT) and glutathione peroxidase (GSH-Px) in D. melanogaster were investigated for the first time. Results The optimal condition for ultrasonic extraction of antioxidant flavonoids from Epimedium pubescens was achieved and extraction mechanism was discussed. Epimedium flavonoids contained icariin, epimedin A, epimedin B and epimedin C. Epimedium flavonoids exhibited the ability to scavenge ABTS+ and DPPH⋅ radicals with EC50 values of 55.8 and 52.1 µg/ml, respectively. Moreover, Epimedium flavonoids were able to increase activities of CAT and GSH-Px in D. melanogaster. For females, oral administration of flavonoids improved CAT and GSH-Px activities by 13.58% and 5.18%, respectively. For males, oral administration of flavonoids increased CAT and GSH-Px activities by 13.90% and 5.65%, respectively. Conclusion Flavonoids ultrasonically extracted from E. pubescens considerably affected antioxidant defense system in D. melanogaster. Flavonoids of E. pubescens showed great potential for becoming a natural antioxidant because of their antiradical ability and effects on CAT and GSH-Px of the model organism.
Keywords: Flavonoids; Epimedium pubescens; Ultrasonic extraction; Antioxidant property; Drosophila melanogaster